2014
DOI: 10.1002/pon.3652
|View full text |Cite
|
Sign up to set email alerts
|

Providing care to a child with cancer: a longitudinal study on the course, predictors, and impact of caregiving stress during the first year after diagnosis

Abstract: The present study suggests that caregiving stress is an important factor in understanding parental adjustment to childhood cancer. This offers possibilities for developing interventions aimed at preventing caregiving stress, and strengthening mothers' confidence in their ability to provide good care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
3
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 48 publications
6
48
3
8
Order By: Relevance
“…Inappropriate behavior of the child [14] and caregiving demands have been identified as predictors of stress [15]. Family circumstances, such as single marital status or the ill child being an only child were also found to predict caregiver burden [16]. The majority of studies identified in a recent meta-analysis on parenting stress focused only on predictors related to a single condition, and most studies focused on asthma, diabetes, cancer, or cystic fibrosis [17].…”
Section: Introductionmentioning
confidence: 99%
“…Inappropriate behavior of the child [14] and caregiving demands have been identified as predictors of stress [15]. Family circumstances, such as single marital status or the ill child being an only child were also found to predict caregiver burden [16]. The majority of studies identified in a recent meta-analysis on parenting stress focused only on predictors related to a single condition, and most studies focused on asthma, diabetes, cancer, or cystic fibrosis [17].…”
Section: Introductionmentioning
confidence: 99%
“…El estudio longitudinal de Sulkers et al (2015) realizado en Holanda, también reportó resultados similares, encontrando que las mamás solteras y las mamás con un solo hijo que fungían como cuidadoras primarias, destacaron con los puntajes más altos de estrés. En esta investigación, se puede observar que la submuestra de cuidadoras que tienen un solo hijo presentan altos niveles de estrés, mientras que las que tienen más de un hijo reportan estar equilibradas.…”
Section: Conclusiónunclassified
“…Uno de estos estudios es el realizado en Holanda por Sulkers et al (2015), el cual reportó que las mamás solteras y las mamás con un solo hijo que fungían como cuidadoras primarias de ñiños/niñas con diagnóstico de cáncer, destacaron con los puntajes más altos de esta variable.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Some patients similarly express concern over accessing frightening or confusing information whereas others report feeling more involved and knowledgeable about their health through portal usage . Caregivers of children with cancer have increased anxiety in response to their child's diagnosis and treatment . Allowing swift access to results may reduce this level of anxiety; however, access to material not intended for a lay audience could also exacerbate anxiety and cause harm.…”
Section: Introductionmentioning
confidence: 99%